Relevant biochemical markers of recovery process in soccer - Marqués-Jiménez, D.; Calleja-Gonzalez, J.; Arratibel, I.; Terrados, N. (Archivos de medicina del deporte, 2016)
Training and competition provide an opportunity to enhance the performance of football players, so is essential to face every training session or competition in the best possible condition. For our knowledge, there are still doubts about the causes and mechanisms underlying fatigue and recovery in football, hence the complexity of monitoring this process. A variety of biomarkers are used nowadays (performance, perceptual and biochemical), but some may not be suitable due to the probable fatigue caused that could influence the recovery process. Despite the difficulty of obtain them in some categories where is not plausible, the information of biochemical markers should be considered whenever was possible. Since its assessment let to optimize the balance between competitive stress and recovery of football players, the aim of this review is to analyze the importance of control, monitoring and evaluate different biochemical markers of recovery in soccer players. Even so, the high variability in their response due to the individual characteristics of players and the metabolic and physiological differences caused by a soccer match or training stop us from monitoring the recovery process in soccer using only one biochemical marker, it is necessary to assess several markers together. In fact, they should be considered as an option to complement the information obtained through physical performance and perceptive markers.